Can taking the perspective of an expert debias human decisions? The case of risky and delayed gains - Białek, Michał; Sawicki, Przemysław (Frontiers in Psychology, 2014)
In several reported previously studies, participants increased their normative correctness after being instructed to think hypothetically, specifically taking the perspective of an expert or researcher (Beatty & Thompson 2012, Morsanyi & Handley 2012). The goal of this paper was to investigate how this manipulation affects risky or delayed payoffs. In two studies, participants (n=193) were tested online (in exchange for money) using the adjusting procedure. Individuals produced certain/immediate equivalents for risky/delayed gains. Participants in the control group were solving the problem from their own perspective, while participants in the experimental group were asked to imagine “what would a reliable and honest advisor advise them to do.” Study 1 showed that when taking the perspective of an expert, participants in experimental group became more risk aversive compared to participants in the control group. Additionally, their certain equivalents diverged from the Expected Value (EV) to a greater extent. The results obtained from the experimental group in Study 2 suggest that participants became less impulsive, which means they tried to inhibit their preferences. This favors the explanation, which suggests that the perspective shift forced individuals to override their intuitions with the social norms. Individuals expect to be blamed for impatience or risk taking thus expected an expert to advise them to be more patient and risk aversive.